Regional Differences in Gamma-Aminobutyric Acid and Glutamate Concentrations in the Healthy Newborn Brain - Basu, S.K.; Pradhan, S.; Barnett, S.D.; Mikkelsen, M.; Kapse, K.J.; Murnick, J.; Quistorff, J.L.; Lopez, C.A.; du Plessis, A.J.; Limperopoulos, C. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Gamma-aminobutyric acid and glutamate system disruptions may underlie neonatal brain injury. However, in vivo investigations are challenged by the need for special 1H-MR spectroscopy sequences for the reliable measurement of the neurotransmitters in this population. We used J-edited 1H-MR spectroscopy (Mescher-Garwood point-resolved spectroscopy) to quantify regional in vivo gamma-aminobutyric acid and glutamate concentrations during the early postnatal period in healthy neonates.MATERIALS AND METHODS: We prospectively enrolled healthy neonates and acquired Mescher-Garwood point-resolved spectroscopy spectra on a 3T MR imaging scanner from voxels located in the cerebellum, the right basal ganglia, and the right frontal lobe. CSF-corrected metabolite concentrations were compared for regional variations and cross-sectional temporal trends with advancing age.RESULTS: Fifty-eight neonates with acceptable spectra acquired at postmenstrual age of 39.1 (SD, 1.3) weeks were included for analysis. Gamma-aminobutyric acid (+ macromolecule) (2.56 [SD, 0.1]) i.u., glutamate (3.80 [SD, 0.2]), Cho, and mIns concentrations were highest in the cerebellum, whereas NAA (6.72 [SD, 0.2]), NAA/Cho, Cr/Cho, and Glx/Cho were highest in the basal ganglia. Frontal gamma-aminobutyric acid (1.63 [SD, 0.1]), Glx (4.33 [SD, 0.3]), Cr (3.64 [SD, 0.2]), and Cho concentrations were the lowest among the ROIs. Glx, NAA, and Cr demonstrated a significant adjusted increase with postmenstrual age (β = 0.2–0.35), whereas gamma-aminobutyric acid and Cho did not.CONCLUSIONS: We report normative regional variations and temporal trends of in vivo gamma-aminobutyric acid and glutamate concentrations reflecting the functional and maturational status of 3 distinct brain regions of the neonate. These measures will serve as important normative values to allow early detection of subtle neurometabolic alterations in high-risk neonates.J-DIFFJ-edited difference spectrumGABAgamma-aminobutyric acidGABA+GABA with macromoleculesGluglutamateGSHglutathioneMEGA-PRESSMescher-Garwood point-resolved spectroscopyNDIneurodevelopmental impairmentNSnot significantPMApostmenstrual ageTEAterm-equivalent age